Development of an Environment Based Chemistry Practicum Guide for Class XI - Faderina Komisia; Maria Benedikta Tukan; Maria Aloisia Uron Leba; Maximus M. Taek; Nikola Tolentini; Maria Sonyatania Iju; Lusiana F. Nggepe (JCER (Journal of Chemistry Education Research), 2025)
This study aims to determine the feasibility of an environmentally based chemistry practicum guide for class XI and to determine student responses to an environmentally based chemistry practicum guide for class XI. The sample in this study was the class XI students of Senior High School 12 Kupang. The type of research used is R&D research using the Thiagarajan 4D development model which consists of defining, designing, developing, disseminating. Based on the results of the material expert validation, the average percentage of validity was 82,22% with very feasible criteria and the media expert validation obtained an average percentage of validity of 85,625% with very feasible criteria. In the limited trial, the average percentage of student responses to the developed practicum guide was 81,13% with very good criteria. In the extensive trial, the average percentage of student responses to the developed practicum guide was 85,42% with very good criteria.